Rancang Bangun Aplikasi Penjualan Berbasis Web (Studi Kasus: Optik Airlangga Surabaya) - Bagus Satria Wibawa; M.J. Dewiyani Sunarto; Januar Wibowo (Jurnal Sistem Informasi Universitas Dinamika, 2022)
CV. Kariyono Mandiri is a company engaged in trade and services under the name Optik Airlangga. The company has four (4) Optical branches, namely the Srikana branch as the central branch which is located at Jl. Srikana no.36 Surabaya, Royal Plaza Surabaya branch, Pandaan branch and Krian branch located on Jl. Basuki Rahmat no. 49 Krian. There is a problem where so far the sales data reported to optical owners is only limited to sales reports, there is no classification of data such as valid goods which are categorized into sub-categories (frames, lenses, accessories) so that optical owners find it difficult to determine which items should be reordered. . To overcome the problems at Optik Airlangga, an application is needed that can help record sales transactions, provide a recap of sales data without having to wait for reports from each branch, and can help optical owners by providing information in the form of best-selling items, total branch sales, and items with profits. that can be used as a consideration for the purchase of goods. After carrying out the stages from analysis to deployment, an application is produced that can record sales transactions, manage master data in the form of item data, item categories, employees, branches. The application provides transaction data that is paid off / not paid off. The application created has also provided a dashboard that provides information on low stock items for cashiers and admin staff. The application displays a dashboard for owner users that displays a graph of the number of sales for each branch, a graph of the best-selling items, and the items with the greatest profits.